Conservation priorities in the Southern Central Andes: mismatch between endemism and diversity hotspots in the regional flora - Godoy Bürki, Ana Carolina (2014)
North western Argentina, the southernmost portion of the tropical Andes, contains one of the main areas of endemism within the Southern Cone, as well as one of the main diversity hotspots of the country. Historically its reserve area systems have been located in the richest ecoregion of the area; the Southern Andean Yungas. We evaluated the effectiveness of the current protected areas in preserving the endemic flora of the region. The distributions of 505 endemic species were either modeled or included as observed data to determine endemism hotspots in each ecoregion. The endemic species were mainly found in arid ecoregions such as the High Monte and the Central Andean Puna, as well as in the transition zones between these regions and the Southern Andean Yungas. We found that more than 1/3 of the endemic species are unprotected in their entire ranges by the current system, while nearly half of the species are protected in only 5 % of their distribution ranges. New priority areas were chosen to increase the effectiveness based on the irreplaceability concept. We show that adding 251 new cells of 100 km2 each would improve the protection values and convert the system to effective. The present paper highlights that priorities set on the basis of species richness may not successfully conserve areas of high plant endemism. However, zoologist would have to realize similar assessments in the endemic fauna in order to find the optimal designed of protected areas system to conserve both the endemic flora and fauna in the Southern Central Andes.